Integrative multi-omics data from early development to identify the genes and cell types underlying attention-deficit/hyperactivity disorder - Shufen Jiao; Li Bao; Xiaowen Lu; Yong Wu; Yichen Li (BMC Psychiatry)
Abstract Background Genome-wide association studies (GWASs) have identified numerous loci significantly associated with attention-deficit/hyperactivity disorder (ADHD); however, the majority of these loci are located in non-coding regions, limiting our understanding of the disorder’s underlying pathogenesis. Methods We applied the summary data-based Mendelian randomization (SMR) approach to integrate expression quantitative trait loci (eQTL) data derived from bulk post-mortem tissues, fetal brain tissues, and single-cell types from induced pluripotent stem cell (iPSC)-derived neurons and post-mortem brain samples with ADHD GWAS data. Additionally, we performed cell-type enrichment analysis to identify specific cell types implicated in ADHD. Results Our integrative analysis identified LSM6 and RPS26 as significantly associated with ADHD, based on eQTL data from fetal brain and iPSC-derived neurons. Genes highlighted in fetal brain and iPSC-derived neurons showed high expression levels during early development, whereas genes identified from post-mortem brain samples tended to be expressed at low levels before the peak onset period of ADHD. Furthermore, cell-type enrichment analysis revealed that SNP-based heritability for ADHD was predominantly enriched in excitatory glutamatergic neurons, with relatively lower enrichment observed in glial cells. Conclusions The findings highlight the importance of considering developmental gene expression dynamics in integrative analyses. Genetic variants may contribute to ADHD pathogenesis by modulating gene expression in the fetal brain, thereby impacting early neurodevelopmental processes.